Smart Bi-directional Soil Parameter Monitoring using GSM Based Multi-Level Alarming (International Journal of Communication Systems and Network Technologies, 2021)
The higher productivity from soil can we achieve through Wireless Sensor Networks (WSNs) technology due to this reason implementation of WSN in precision agriculture is increasing day by day. Among the different technologies for crop monitoring (WSNs) are recognized as a powerful one to collect and process data in the agricultural domain, with low-cost and low-energy consumption. The proposed system will use Global System for Mobile (GSM) technology for automatically monitor the parameter of soil. It transfer the soil data over the mobile network using the GSM modem. Under the hardware part sensors node units were developed. Which is used for fetching and loading data through the energy efficient GSM and this Bi-directional multi-level text messaging option to improve the efficiency of alarming system. The system contains pair of sensor like ph and humidity used to monitor collected soil data from sensors by the microcontroller. This paper focus different challenges and uses encounter and also discuss different results obtain by monitoring the various soil parameters in the real time Agriculture environment.
Keywords: Wireless Sensor Networks; Soil Parameter Monitoring; GSM; Precision Agriculture; Soil Moisture; Sensor; pH Value Analysis; Multi-Level Alarming; Arduino